Efektivitas Penurunan Kekeruhan Air dengan Media Saringan Pasir Silika dan Karbon Aktif - Suharyono Fajar Febrianto; Ana Yustika; Verry Aji Kurniawan; Ana Khoirul Ummah; Aprin Wahyu Wijayanti (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2025)
Clean water is a very important basic need in daily life because it is used for household purposes, health, and other activities. Good water quality is determined by several physical, chemical, and biological parameters. One of the physics parameters that is often used is the level of turbidity of the water. Cloudy water not only reduces aesthetic value, but also has the potential to carry suspended solid particles and microorganisms that can cause health problems. Therefore, efforts are needed to reduce the level of turbidity of water to meet clean water quality standards. This study aims to determine the comparison of the effectiveness of the use of silica sand filters with silica sand filters combined with activated carbon in reducing water turbidity. This type of research is an experimental research with a three-stage procedure, namely the manufacture of filters, filtration processes, and measurement of water turbidity using turbidity meters. Each treatment group was measured 30 times to obtain representative results. The results of the study showed that the use of silica sand filters was able to reduce water turbidity with an average effectiveness of 81.4%. Meanwhile, the combination of silica sand and activated carbon filters was only able to reduce turbidity by an average of 65.7%. This shows that silica sand media is more effective than the combination of silica sand and activated carbon in reducing water turbidity. This finding is expected to be a reference in the application of simple clean water treatment technology in the community, especially in areas that still experience limited access to quality clean water.